Social and religious institutions of the Tlhaping of the Taung reserve. - Pauw, Berthold Adolf (Social Anthropology, 2015)
The thesis is a study of present-day religion in a rural Bantu society, viewed within the framework of their social structure. The society is that of the Tlhaping of the Phuduhtswana chiefdom of the Taung reserve. After an introductory chapter on the historical and geographical background, a chapter is devoted to the social and economic changes that have taken place or are still taking place, such as the scattering of the population from a large central capital, the concomitant changes in political organisation, the weakening of kinship ties, and the participation in migrant labour. By far the most prominent type of religion in this society to-day is that represented by the Christian churches, and the major part of this study therefore deals with the churches, but in a separate chapter the remnants of pagan belief and ritual are also discussed.